Interações e novas práticas sociais: um estudo multietnográfico nos espaços públicos de acesso pago à internet em novo Hamburgo - Miranda, Luís Marcelo (Universidade do Vale do Rio dos Sinos, 2010)
In the current phase of the information society, the urban space and how communication goes through major changes. The ways of designing the space are consequences of network environments, the Internet. This search discusses the interaction and new social habits in public spaces with paid access to the Internet downtown in Novo Hamburgo. For this, raises the multiethnograpy, a method that combines ethnography, photoethnography,and netnography simultaneously. In the countryside, cafes (with wi-fi), cybercafés, and lanhouses are observed, reported and discussed some of the characteristics of those places, which can be viewed as aggregations to cyberspace. Concrete examples are shown from photographs on the places, and urban notes describing the reality of online and offline spaces that serve as the link between physical and virtual. They are places where contemporary sociability happen, emerging from new forms of socialization, new lifestyles and new forms of social organization.
Keywords: Interações; Práticas sociais; Multietnografia; Espaços de acesso pago à Internet; Interaction; Social practices; Multiethnograpy; Places with paid access to the Internet; ACCNPQ::Ciências Sociais Aplicadas::Comunicação